2010
DOI: 10.1510/icvts.2009.217356
|View full text |Cite
|
Sign up to set email alerts
|

Briefing and debriefing in the cardiac operating room. Analysis of impact on theatre team attitude and patient safety

Abstract: Error in health services delivery has long been recognised as a significant cause of inpatient morbidity and mortality. Root-cause analyses have cited communication failure as one of the contributing factors in adverse events. The formalised fighter pilot mission brief and debrief formed the basis of the National Aeronautics and Space Administration (NASA) crew resource management (CRM) concept produced in 1979. This is a qualitative analysis of our experience with the briefing-debriefing process applied to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 10 publications
4
24
0
4
Order By: Relevance
“…19 Our results indicate that despite the value placed on PRD by health care providors, PRD in Canadian pediatric EDs is underdeveloped, infrequently used, and insufficiently supported. Although there is growing evidence of the positive effect of debriefing after surgical, anesthetic, or critical care-based simulation events, [20][21][22][23][24][25][26][27][28] there is a lack of evidence on how PRD impacts teamwork and patient care in the ED. Our findings are consistent with an Australian study of pediatric ED physicians and nurses that identified a perceived need but a lack of a structured debriefing process.…”
Section: Current Practice and Identified Obstaclesmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Our results indicate that despite the value placed on PRD by health care providors, PRD in Canadian pediatric EDs is underdeveloped, infrequently used, and insufficiently supported. Although there is growing evidence of the positive effect of debriefing after surgical, anesthetic, or critical care-based simulation events, [20][21][22][23][24][25][26][27][28] there is a lack of evidence on how PRD impacts teamwork and patient care in the ED. Our findings are consistent with an Australian study of pediatric ED physicians and nurses that identified a perceived need but a lack of a structured debriefing process.…”
Section: Current Practice and Identified Obstaclesmentioning
confidence: 99%
“…The effectiveness of debriefing on achieving learning objectives has been studied, mostly outside the ED. [20][21][22][23][24][25][26][27][28] Simulation provides an active learning environment for health care providers to experience clinical situations and use cognitive, technical, and affective skills, such as those used in real-life resuscitation scenarios. 7,35 Systematic reviews of simulation literature identified feedback as the most important feature of simulation-based medical education.…”
Section: Training In Debriefingmentioning
confidence: 99%
“…Os indicadores de processo permitem avaliar a forma como um protocolo de cuidados de saúde é realizado ou prestado (5) . Dos artigos analisados são realçados instrumentos relevantes da área dos processos da avaliação da qualidade (11)(12)(13)(14)(15)(16)(17) .…”
Section: Avaliação Do Processounclassified
“…Os conceitos "briefing e debriefing" são aplicados no estudo B6 (16) . Estes instrumentos têm sido utilizados entre os pilotos comerciais e de combate, e foram formalizadas para formação pela National Aeronautics and Space Administration (NASA), e agora aplicados à área da saúde, primeiramente nos blocos operatórios.…”
Section: Avaliação Do Processounclassified
See 1 more Smart Citation